2014
DOI: 10.1386/jdsp.6.2.219_1
|View full text |Cite
|
Sign up to set email alerts
|

Risk and flow in contact improvisation: Pleasure, play and presence

Abstract: Grounded in Csikszentmihalyi’s flow theory, the focus of this study was to examine the role of flow as a framework for optimizing the practice of risk-taking in the teaching and learning of contact improvisation in higher education, and to better enable students to take the creative, physical and psychological risks associated with that practice. A range of qualitative methodologies were employed including observation, analysis, writing, drawing and focus group discussions. Findings of this study included: est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In line with that, Delle Fave et al (2003) found that the opportunity to experience flow motivates climbers to take part in a risky expedition. Urmston and Hewison (2014) also find a positive relationship between flow and risk taking in learning. A study by Szymanski and Henning (2007) found that flow was negatively related to women’s self-objectification behavior.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…In line with that, Delle Fave et al (2003) found that the opportunity to experience flow motivates climbers to take part in a risky expedition. Urmston and Hewison (2014) also find a positive relationship between flow and risk taking in learning. A study by Szymanski and Henning (2007) found that flow was negatively related to women’s self-objectification behavior.…”
Section: Resultsmentioning
confidence: 66%
“…Similar results were found by Ceja and Navarro (2009) who state that flow experiences follow a complex dynamic. In general, and in association with the challenge-skill balance, having enough resources ( Delle Fave and Bassi, 2009 ; Bakker et al, 2011 ) and risk or uncertainty ( Urmston and Hewison, 2014 ) are associated with flow. Another example for a flow-promoting fit between the context and the individual was shown by Vittersø et al (2001) , who found that a fit between individual’s preferred recreational mode and the recreational activity (e.g., being active or passive) was positively associated with flow.…”
Section: Resultsmentioning
confidence: 99%
“…In line with that, Delle Fave et al (2003) found that the opportunity to experience flow motivates climbers to take part in a risky expedition. Urmston and Hewison (2014) also find a positive relationship between flow and risk taking in learning. A study by Szymanski and Henning (2007) found that flow was negatively related to women's selfobjectification behavior.…”
Section: Other Forms Of Behaviormentioning
confidence: 66%
“…The most significant factor positively influencing purchase intent is the pleasure and enjoyment aspect of the book (Ozkara et al, 2017;Shahpasandi et al, 2020;To & Sung, 2015). When people are in a state of flow, they are less inclined to consider the practical ramifications of their activities and more likely to concentrate on their enjoyment of the activity (Urmston & Hewison, 2014). Literature indicates that shoppers experiencing high levels of flow are more likely to participate in hedonic activities (Bridges & Florsheim, 2008;Ozkara et al, 2017;Schmitt, 1999).…”
Section: Introductionmentioning
confidence: 99%